Health research funding: obtaining grants. Tips to improve the success rate. Part 2 - Herrera, Víctor; Posadas-Martínez, María Lourdes (Revista del Hospital Italiano de Buenos Aires, 2022)
This is the second part of our series on searching funds for a research plan. Every research proposal requires a source of funding to be carried out. Looking for funds is a time and effort consuming task with a low success rate. We share some tips that may help to improve that success rate related to (1) how to recognize the need of an external funding source, (2) where the funds are coming from, (3) what costs can be funded and (4) how to improve a proposal writing and submission
Keywords: health financing; medical research; economics